Conserved chloroplast open-reading frame ycf54 is required for activity of the magnesium protoporphyrin monomethylester oxidative cyclase in synechocystis PCC 6803 - Hollingshead, S; Kopecna, J; Jackson, P; Canniffe, D; Davison, P; Dickman, M; Sobotka, R; Hunter, C (American Society for Biochemistry and Molecular Biology, 2012)
The cyclase step in chlorophyll (Chl) biosynthesis has not been characterized biochemically, although there are some plausible candidates for cyclase subunits. Two of these, Sll1214 and Sll1874 from the cyanobacterium Synechocystis 6803, were FLAG-tagged in vivo and used as bait in separate pulldown experiments. Mass spectrometry identified Ycf54 as an interaction partner in each case, and this interaction was confirmed by a reciprocal pulldown using FLAG-tagged Ycf54 as bait. Inactivation of the ycf54 gene (slr1780) in Synechocystis 6803 resulted in a strain that exhibited significantly reduced Chl levels. A detailed analysis of Chl precursors in the ycf54 mutant revealed accumulation of very high levels of Mg-protoporphyrin IX methyl ester and only traces of protochlorophyllide, the product of the cyclase, were detected. Western blotting demonstrated that levels of the cyclase component Sll1214 and the Chl biosynthesis enzymes Mg-protoporphyrin IX methyltransferase and protochlorophyllide reductase are significantly impaired in the ycf54 mutant. Ycf54 is, therefore, essential for the activity and stability of the oxidative cyclase. We discuss a possible role of Ycf54 as an auxiliary factor essential for the assembly of a cyclase complex or even a large multienzyme catalytic center.